AmpC β-lactamases producing Gram-negative clinical isolates from a tertiary care hospital - Shubhdeep Kaur; Veenu Gupta; Deepinder Chhina (Wolters Kluwer Medknow Publications, 2016)
Introduction: AmpC βlactamases are clinically significant since these confer resistance to cephamycins as well as other extended-spectrum cephalosporins and are not affected by βlactamase inhibitors. Objectives: This prospective study was planned to detect AmpC producers among Gram-negative clinical isolates and to compare drug resistance in AmpC and non-AmpC producers. Materials and Methods: In this 1-year prospective study, all Gram.negative isolates were identified by colony characteristics, Gram.staining, biochemical reactions as per standard procedures. Antimicrobial susceptibility was done by as per Clinical and Laboratory standards Institute guidelines. The AmpC was detected by AmpC disc test. Results: Of 2100 samples received, 581 samples showed growth of Gram-negative isolates. Monomicrobial growth was seen in 79.8% and polymicrobial in 20.1%. There were 711 Gram-negative isolates. Of which Acinetobacter baumannii (32.5%), Klebsiella pneumoniae (29.2%), and Pseudomonas aeruginosa (22.3%) were common. Antimicrobial susceptibility pattern showed increased sensitivity toward carbapenems, polymixin B, and tigecycline. AmpC- β-lactamase production was seen in 13.3% isolates and AmpC producers showed high resistance to various antimicrobial agents as compared to non-AmpC producers. Conclusion: Majority of Gram-negative isolates were multidrug resistant and AmpC production was seen in 13.3% isolates. A. baumannii and K.pneumoniae showed maximal AmpC production. AmpC testing is therefore recommended as a mandatory test in a hospital set up.